2018
DOI: 10.1021/acs.jpcc.8b07078
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Enhanced Autocatalytic N-Demethylation

Abstract: Increasing experimental results indicate that optically excited plasmonic metal nanoparticles can drive photochemical reactions at photon flux comparable to that of solar radiation. However, experimental evidence that provides insight into the mechanism of the reactions on plasmonic surfaces has been limited. Here, using plasmon-enhanced N-demethylation (PEND) of methylene blue (MB) as model reaction, we report mechanistic analysis of photochemical reactions on plasmonic gold nanoparticles under different adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(65 citation statements)
references
References 76 publications
3
62
0
Order By: Relevance
“…Different photochemical N -dealkylation methods using various photocatalysts have been developed for the synthesis of various N -dealkylated chemicals [ 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 ]. An early report by Pandey et al [ 160 ] showed that the photolysis of a tertiary N -methyl amine using dicyanonaphtalene 128a as electron acceptor in the presence of sodium hydroxide in methanol led to high yields of N -demethylated products ( 51c , 94c , 129c , and 130c ) ( Figure 18 ).…”
Section: Photochemical N -Dealkylationmentioning
confidence: 99%
“…Different photochemical N -dealkylation methods using various photocatalysts have been developed for the synthesis of various N -dealkylated chemicals [ 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 ]. An early report by Pandey et al [ 160 ] showed that the photolysis of a tertiary N -methyl amine using dicyanonaphtalene 128a as electron acceptor in the presence of sodium hydroxide in methanol led to high yields of N -demethylated products ( 51c , 94c , 129c , and 130c ) ( Figure 18 ).…”
Section: Photochemical N -Dealkylationmentioning
confidence: 99%
“…Recently, the plasmon-driven polymerization of thiols was visualized through TERS . Other interesting demonstrations include tracking tautomerization of porphycene at plasmonic hotspots, plasmon-enhanced N-demethylation of methylene blue, photoinduced and plasmon-driven cis–trans isomerization, , and photocatalytic reduction of CO 2 following visible light irradiation . The oxidative and reductive dimerization of p -nitrothiophenol (NTP) and p -aminothiophenol (ATP) to dimercaptoazobenzene (DMAB) on plasmonic substrates is of particular relevance to this work and has been extensively scrutinized by several groups. Although controversial in its early days, subsequent analyses of these dimerization processes convincingly established plasmon-enhanced DMAB formation.…”
mentioning
confidence: 99%
“…The larger wavelength shift and broadening for thionine than for MB can be attributed to the replacement of the relatively bulky methyl groups at the N-terminus with hydrogen atoms that favors stronger thionine–surface interaction through the amine functional groups because there is less steric hindrance as the adsorption geometry reported by Guo et al suggests . The stronger surface–molecule interaction for thionine than for MB can be the thermodynamic driving force for the plasmon-driven N-demethylation of MB. ,, …”
mentioning
confidence: 93%
“…34 The stronger surface−molecule interaction for thionine than for MB can be the thermodynamic driving force for the plasmon-driven N-demethylation of MB. 32,36,48 The absorbance changes observed as a function of adsorption time are analyzed on the basis of adsorption isotherms obtained using the integral area under the curves in panels b and d of Figure 3. To facilitate the analysis, we define an adsorption parameter as η = I t /I m , where I t and I m are the integral areas at any time (t) and infinite time when a monolayer (m) surface coverage is assumed, respectively.…”
mentioning
confidence: 99%